OPTIMIZATION OF FASHION RETAIL CUSTOMER DATA MANAGEMENT THROUGH EXPLORATORY DATA ANALYSIS AND RECENCY, FREQUENCY, MONETARY - Yusuf, Yusuf; Basri, Lody Saladin; Hastomo, Widi; Wardhani, Ire Puspa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This study was conducted to analyze revenue patterns, product segmentation, and customer retention in the H&M retail business using Kaggle competition data